Effect of the techniques of karate on functional status and physical fitness of students of Flight Academy - Галімський Володимир Олександрович (Volodymir Galimskyi) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to investigate the effect of the application of the techniques of karate on functional status and physical fitness of students of Flight Academy first year. Material and Methods: the study involved students of Flight Academy EG (pilots, n=25) and CG (rescuers, n=23). We determined the effect of the techniques of karate in physical fitness, running the 100 meters, bending and unbending hands ups, pull-ups on the bar, running 3,000 meters, 10 revolutions per gymnastic wheel; on functional status, body length, body weight, heart rate at rest, vital capacity, vital index (ml·kg–1) sample and test Stange and Ghencea. Results: revealed that the use of uniform and alternating load of running helped improve the outcome for 3000 m run and function of the respiratory system. Anaerobic subject to the techniques of karate contributed to increasing resistance to hypoxia. Conclusions: this study suggests the need to improve physical fitness of students by implementing motor activity of certain sports